Facilitators of and barriers to implementing a traditional Chinese medicine collaborative model of care for axial spondyloarthritis: a qualitative study. Issue 6 (December 2021) - Kwan, Yu Heng; Fong, Warren; Ang, Xiang Ling; Chew, Xiu Yan; Yoon, Sungwon; Tan, Chuen Seng; Tai, Bee Choo; Huang, Youyi; Bilger, Marcel; Phang, Jie Kie; Tan, Hui Chin; Quek, Su-An; et al.
Background: Conventional therapy may be inadequate for many patients with axial spondyloarthritis (axSpA). Traditional Chinese medicine (TCM) may be a viable alternative, but its effectiveness for axSpA is unknown. We are currently conducting a pragmatic randomised controlled trial (RCT) to investigate the effectiveness of a TCM collaborative model of care (TCMCMC), which combines usual rheumatologic care with acupuncture for patients with axSpA. This nested qualitative sub-study aims to identify facilitators of and barriers to the implementation of the TCMCMC. Methods: We conducted individual in-depth interviews with participants who had completed the acupuncture regimen to elicit opinions on the facilitators of and barriers to the implementation of the TCMCMC. The interviews were transcribed and analysed using thematic analysis. Results: Twelve participants were included, with data saturation occurring after 10 interviews. The analysis revealed both a number of important 'facilitators' and 'barriers'. Facilitators to the implementation of the TCMCMC included effectiveness of TCM to relieve symptoms, inadequacy of conventional treatment and positive social perceptions of TCM. Barriers included scepticism towards TCM, inability of TCM to provide instant relief, needle-related discomfort, variable effectiveness of TCM influenced by physicians' skills and experience and the high cost of TCM. Recommendations to overcome barriers included further patient education about TCM. Conclusion: Policymakers should take into account the various feasibility factors identified in this study when developing and implementing a TCMCMC. Trial registration number: NCT03420404 (ClinicalTrials.gov)